2020
DOI: 10.1002/cche.10387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hericium erinaceus powder on the digestion, gelatinization of starch, and quality characteristics of Chinese noodles

Abstract: Background and objectives To improve the nutritional value and flavor of traditional Chinese noodles, Hericium erinaceus powder (HEP) was incorporated into Chinese noodles. The effects of HEP on the digestion, gelatinization of starch, and quality characteristics of Chinese noodles were analyzed. Findings The results showed that adding HEP could significantly reduce starch digestion rate and digestion extent in noodle, and the antioxidant capacity and gelatinization temperature were also positively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…During heat treatment, starch may turn to dextrin and drying methods affects available carbohydrate content. Besides, the conversion degree of crystalline structure of the starch granule and gelatinization rate occurs depending on the temperature used, proportions of amylose and amylopectin and water content in the mushroom samples (Wang et al) [ 17 ]. The importance of starch gelatinization and retrogradation is important in case food industrialist want to apply dried mushroom as functional food.…”
Section: Resultsmentioning
confidence: 99%
“…During heat treatment, starch may turn to dextrin and drying methods affects available carbohydrate content. Besides, the conversion degree of crystalline structure of the starch granule and gelatinization rate occurs depending on the temperature used, proportions of amylose and amylopectin and water content in the mushroom samples (Wang et al) [ 17 ]. The importance of starch gelatinization and retrogradation is important in case food industrialist want to apply dried mushroom as functional food.…”
Section: Resultsmentioning
confidence: 99%
“…The cooking properties of noodles were determined by previously reported methods [ 13 ]. Raw noodles (10 g) were put into 500 mL of boiling distilled water for the optimal cooking time, and the optimal cooking time was defined as the time at which the white core in the central portion of the noodle strand disappeared when the noodle was squeezed between two transparent glass plates.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, people pay more attention to natural, functionally healthy food. The results showed that the addition of fungus could strengthen noodles’ quality and nutritional characteristics [ 12 , 13 ]. If TF can be added to noodles as a thickening agent, it could improve the quality of the noodles, slow down the digestion of starch in noodles, avoid the rapid rise of blood sugar after meals, help prevent the occurrence of diabetes, and enrich the flavor of noodles.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, wheat flour has been used as the main raw material for noodle preparation. Recently, to enrich the flavour, nutrition, and character of noodles, other staple foods, including vegetables, fruits, mushrooms and plants, such as oats [ 1 ], buckwheat [ 2 ], sweet potato [ 3 ] Hericium erinaceus [ 4 ], pitaya peel [ 5 ] and so on, have been mixed with wheat flour to produce noodles. The addition of potato flour improved the pasting characteristics of the dough and the water absorption, hardness, and elasticity of the noodles, but destroyed the gluten network structure of the dough and reduced the texture of the noodles [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The addition of potato flour improved the pasting characteristics of the dough and the water absorption, hardness, and elasticity of the noodles, but destroyed the gluten network structure of the dough and reduced the texture of the noodles [ 6 ]. Shiitake mushroom powder and dragon fruit peel powder could improve the color, total polyphenol content, and antioxidant activity of the noodles [ 4 , 5 ]. The addition of buckwheat can improve the quality of noodles, and also increase the total phenol content, total flavonoid content and antioxidant capacity of the noodles [ 2 ].…”
Section: Introductionmentioning
confidence: 99%